Geochemistry Characterization of Alkaline Syenite from Pakkanadu Alkaline Carbonatite Complex, Ultramafic rocks from in Southern Granulite Terrain - P. Gangatharan, 2K. Anbarasu (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Pakkanadu alkaline Carbonatite Complex (PASC)occurs in Southern Granulite Terrain (SGT) contains many rock formations from mafic to ultramafic composition. Twenty samples were collected randomly to assess the textural characteristics and trace elemental concentration of the alkaline rocks from Pakkanadu complex, mafic rocks from the Chalk Hill Complex of SGT, Salem, India.The Photomicrograph study discloses the presence of felsic minerals (Alkali feldspar and Nepheline) and mafic minerals (Olivine and Pyroxene) in the collected examples. The petrography result shows that both crustal and mantle-derived rock compositions and their texture demonstrate their source. The elemental distribution in alkaline and mafic rock is controlled by the process of magma differentiation.